Binge alcohol consumption leading to hypokalemic rhabdomyolysis. Issue 5 (23rd May 2019) - Mahendran, Manjit; Agarwal, Shubham; Ray, Animesh; Vikram, Naval Kishore
Abstract : A 43-year-old man presented with acute onset rapidly progressive weakness in all four limbs (proximal greater than distal), following an episode of binge alcohol ingestion, and was admitted for evaluation and management. There was a history of decreased urine output since 2 days with dark-coloured urine. He was found to have severe hypokalemia and renal dysfunction. Serum creatine kinase was significantly high, and further investigation revealed significantly elevated serum and urine myoglobin levels suggestive of rhabdomyolysis, which was secondary to severe hypokalemia. Following supplementation with intravenous and oral potassium and supportive care, the weakness improved significantly, and he was subsequently discharged. This case describes severe hypokalemia, resulting in rhabdomyolysis and generalised lower motor neuron weakness, in a setting of binge alcohol ingestion, which is an entity rarely described in literature.